Rapid response to cyclosporin A and favorable renal outcome in nongenetic versus genetic steroid-resistant nephrotic syndrome - Büscher, Anja K.; Beck, Bodo B.; Melk, Anette; Hoefele, Julia; Kranz, Birgitta; Bamborschke, Daniel; Baig, Sabrina; Lange-Sperandio, Bärbel; Jungraithmayr, Theresa; Weber, Lutz T.; Kemper, Markus J.; Tönshoff, Burkhard; et al. (Clinical journal of the American Society of Nephrology, 2015)
Background and objectives Treatment of congenital nephrotic syndrome (CNS) and steroid-resistant nephrotic syndrome (SRNS) is demanding, and renal prognosis is poor. Numerous causative gene mutations have been identified in SRNS that affect the renal podocyte. In the era of high-throughput sequencing techniques, patients with nongenetic SRNS frequently escape the scientific interest. We here present the long-term data of the German CNS/SRNS Follow-Up Study, focusing on the response to cyclosporin A (CsA) in patients with nongenetic versus genetic disease. - Design, setting, participants, & measurements Cross-sectional and longitudinal clinical data were collected from 231 patients with CNS/SRNS treated at eight university pediatric nephrology units with a median observation time of 113 months (interquartile range, 50-178). Genotyping was performed systematically in all patients. - Results The overall mutation detection rate was high at 57% (97% in CNS and 41% in SRNS); 85% of all mutations were identified by the analysis of three single genes only (NPHS1, NPHS2, and WT1), accounting for 92% of all mutations in patients with CNS and 79% of all mutations in patients with SRNS. Remission of the disease in nongenetic SRNS was observed in 78% of patients after a median treatment period of 2.5 months; 82% of nongenetic patients responded within 6 months of therapy, and 98% of patients with nongenetic SRNS and CsA-induced complete remission (normalbuminemia and no proteinuria) maintained a normal renal function. Genetic SRNS, on the contrary, is associated with a high rate of ESRD in 66% of patients. Only 3% of patients with genetic SRNS experienced a complete remission and 16% of patients with genetic SRNS experienced a partial remission after CsA therapy. - Conclusions The efficacy of CsA is high in nonhereditary SRNS, with an excellent prognosis of renal function in the large majority of patients. CsA should be given for a minimum period of 6 months in these patients with nongenetic SRNS. In genetic SRNS, response to CsA was low and restricted to exceptional patients.